(untitled) (Contemporary Journal of Social Science Review, 2025)
Fat-shaming which is the process of stigmatizing and negative treatment of people due to their weight has proven to be a widespread social phenomenon and has serious psychological implications. This paper has discussed how fat-shaming leads to psychological distress and self- esteem disturbance in a group of 300 subjects. Quantitative research design was used whereby a structured questionnaire with Likert-scale questions was used to measure the experiences of fat- shaming to the respondents, the distress, and their self-perception levels. The Pearson correlation and one-way ANOVA were used to analyze the data. The findings suggested that fat-shaming was strongly linked to negative psychological results. In particular, increased fat-shaming was associated with the increased levels of psychological distress and low self-esteem. In addition, large group difference was also noticed implying that those who were highly exposed to weight based stigmatization reported greater psychological effects than those who were not highly exposed. These results point to a negative impact of fat-shaming as a psychosocial stressor that negatively affects mental health and general well-being. The research is an addition to the body of literature that stresses that weight stigma must be viewed as a health issue as opposed to a social behavior. Interventions that have been recommended to address the issue comprise educational programs to break stereotypes in society, incorporation of supportive mental health programs, and the advancement of inclusive practices in healthcare and policy systems. Although the investigation has weaknesses in the form of a cross-sectional study design and application of self- reported instruments, it offers a significant platform upon which subsequent longitudinal and cross-cultural investigations on the psychological effects of fat-shaming can be conducted.